PERANCANGAN MESIN PENGUPAS SABUT KELAPA DENGAN KAPASITAS 360 KG/JAM - Purboyo, Sigit; Hidayat, Amri; Aldrin, Aldrin; Nuryadi, Halid (Jurnal GEAR (Energi, Perancangan, Manufaktur & Material), 2024)
In general, the process of peeling coconut coir still uses a manual process with amachete or crowbar so that it requires a lot of manpower with special skills, long time,and sharp tools to peel coconuts, This research aims to produce the design of a coconutcoir peeling machine, which can help in the process of peeling coconut coir and separatecoconut coir from coconut shells. The method used in this study is the Pahl Beitzmethod which consists of four stages. First, compile product technical specifications tomeet the needs of the community. Second, look for several product concepts in the formof sketches or simple schemes. Third, give shape to the product concept so that theelements can compose the shape of the product. Fourth, determine product details suchas the arrangement of elements, shape, dimensions, surface smoothness, and material.From the results of this study, it was obtained that the drive motor was selected with apower of about 3 HP with a speed of 2200 rpm. For the chain system and sprocket, a chain number of 40 with a single frame was chosen. With the shaft diameter selectedØ20 mm for the drive motor and Ø25 mm for the peeling roller. The calculation resultsshow that the production capacity of coconut fiber peeling is 360 kg/hour, taking intoaccount the number of coconuts per session (10 coconuts), with the average weight ofcoconuts (1.5 kg), and the peeling time per session for (2 minutes).